A case study on low-code integration platforms - Kuismin, Elmeri (My University, 2023)
The low-code approach has been gaining popularity among integration platforms. Low-code aims to make software development so intuitive that regular citizens could build applications. However, there is little research on what effects it has on integration development. This thesis consists of a literature review and a case study. The literature review aims to identify the areas of software that are affected by the low-code approach. Then a case study is conducted with 4 cases and 4 integration platforms to determine how low-code affects the comparison areas. The key advantages of low-code were that the platforms were easier to learn and use, and they improved development times. The disadvantages of low-code were that expanding their functionalities was more difficult and code produced with them could not be reused with other platforms.
Keywords: low-code, integration, integration platform, citizen developer